Consideração a respeito dos estaminóides da flor do cacaueiro ''catongo'' (Theobroma cacao L.) - Shimoya, C (Revista Ceres, 2025)
The so-called "stamenoids" of the "Catongo" cacao flower (Theobroma cacao L.) are appendages of the stamen. Therefore the androecium is isostemonous, monadelphous and can also be called meristemonous. Thus, we conclude that the flower of cacao is typically pentamerous and all the parts of the verticil are alternate.